Implementation of The Freedom Learning Program for Prospective Primary School Teachers at Universitas Negeri Semarang: Opportunities and Challenges - Moh Fathurrahman; Isa Ansori; Sigit Yulianto; Susilo Tri Widodo; Moh Farizqo Irvan; Dyah Krisnawati; Rian Pristiwanto; Jannatun Tri Lestari (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2023)
The Freedom Learning - Freedom Campus (MBKM) Policy is a form of learning in higher education that is autonomous and flexible. However, in implementing the program several challenges and opportunities were encountered. This study aims to describe the challenges and opportunities faced in the implementation of MBKM program in the Primary School Education Department, especially in the student exchange program. The research approach used is qualitative research with a case study research design. Sources of research data are lecturers and students at partner universities as subjects who carry out student exchanges. Data collection techniques used in-depth interviews, participatory observation, documentation, and anecdotal notes. The data analysis technique used is descriptive analysis (data condensation, data display, and verification). The results showed that most of the students experienced challenges related to socio-cultural factors. The use of regional languages during lectures makes students need time to adjust. Regarding opportunities, differences in an academic culture that affect the learning process (course assignments, teaching methods, and use of technology) provide opportunities for each university to be able to adapt an academic culture that has a positive impact. So, more technical guidelines are needed in the implementation of the MBKM student exchange program.